2011
DOI: 10.1038/ncomms1421
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of MITF stability by the USP13 deubiquitinase

Abstract: The microphthalmia-associated transcription factor (MITF) is essential for melanocyte development. Mutation-induced MAPK pathway activation is common in melanoma and induces MITF phosphorylation, ubiquitination, and proteolysis. Little is known about the enzymes involved in MITF ubiquitination/deubiquitination. Here we report the identification of a deubiquitinating enzyme, named ubiquitin-specific protease 13 (USP13) that appears to be responsible for MITF deubiquitination, utilizing a short hairpin RNA libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 35 publications
(57 reference statements)
1
91
2
1
Order By: Relevance
“…USPs represent the largest family of ubiquitin‐deconjugating enzymes. To date, the first well‐studied USP in melanoma was USP13, of which the significant up‐regulation contributed to melanoma growth via deubiquitination and stabilization of melanocyte lineage‐specific transcriptional factor MITF 13. Apart from this, USP8 and USP15 have been reported to act as oncogenic factor in melanoma, highlighting that both ubiquitin‐conjugating and ubiquitin‐deconjugating enzymes played important roles in melanoma tumour biology 31, 32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…USPs represent the largest family of ubiquitin‐deconjugating enzymes. To date, the first well‐studied USP in melanoma was USP13, of which the significant up‐regulation contributed to melanoma growth via deubiquitination and stabilization of melanocyte lineage‐specific transcriptional factor MITF 13. Apart from this, USP8 and USP15 have been reported to act as oncogenic factor in melanoma, highlighting that both ubiquitin‐conjugating and ubiquitin‐deconjugating enzymes played important roles in melanoma tumour biology 31, 32.…”
Section: Discussionmentioning
confidence: 99%
“…For melanoma, the mutations of ubiquitination‐related genes such as BRCA1‐associated protein‐1(BAP1), F‐boxand WD repeat domain‐containing 7 (FBXW7) and PARK2 are frequently identified and participated in melanoma tumourigenesis 11. What is more, the activation of some critical signalling pathways in melanoma development including NF‐κB and MITF are also subtly regulated by ubiquitination,12, 13 demonstrating its vital pathogenic role in melanoma. Notably, previous studies mainly focused on the regulatory role of ubiquitin‐conjugating enzymes, especially E3 ubiquitin ligases in melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…For example, USP13 appears to be responsible for the protein stability of microphthalmia-associated transcription factor, which is essential for melanocyte development (37). USP13 can reduce the ubiquitination and degradation of Sky2, the F-box adaptor of the E3 ubiquitin ligase SCF Skp2 (47).…”
Section: Discussionmentioning
confidence: 99%
“…One biochemical consequence of MAPK pathway activation is the direct phosphorylation of MITF by ERK/MAPK on Ser 73, an effect that was shown to enhance molecular recruitment of the coactivator p300 to MITF Price et al 1998). Another consequence of this MITF phosphorylation is ubiquitination and proteolysis of MITF (Wu et al 2000;Xu et al 2000), an effect recently shown to be antagonized by the deubiquitinase USP13 (Zhao et al 2011). Of note, bacterial artificial chromosomes containing Ser 73-to-alanine mutation of MITF were capable of rescuing coat color/pigmentation of Mitfdeficient mice ).…”
Section: Mitf-melanocyte Master Regulatormentioning
confidence: 99%